PENGARUH PENGGUNAAN WEB GOOGLE SITES DALAM MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Servia Rosmawati; Rendra Gumilar; Raden Roro Suci Nurdianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the problem of student learning outcomes in economics subjects at SMA Negeri 4 Tasikmalaya which were still relatively low. This research aims to determine the effect of using Google Web Sites in the Discovery Learning learning model to improve student learning outcomes. The method used in this research is Quasi experimental with a nonequivalent control group design. The population of this study was all students in class XI IPS at SMAN 4 Tasikmalaya which consisted of 5 classes with a total of 184 students. The sampling technique was purposive sampling, where class XI IPS 4 was the experimental class and XI IPS 5 was the control class. The data collection technique used is a multiple choice test with the data analysis technique used is the paired sample t-test and the independent sample t-test. The test results show that 1) There are differences in the learning outcomes of students in the experimental class through the use of Google Web Sites in the discovery learning learning model before and after treatment. With an N-Gain of 0,77. 2) There are differences in the learning outcomes of students in the control class using the conventional learning model (lecture) before and after treatment. With an N-Gain of 0,56. 3) There is a difference in the increase in learning outcomes between students in the experimental class through the use of Google Web Sites in the discovery learning learning model and control class students who used the conventional learning model (lecture) after treatment. The average posttest score for the experimental class was 85,63 with an N-Gain of 0,77, while the average posttest score for the control class was 73,24 with an N-Gain of 0,56.